PENGEMBANGAN PULAU-PULAU KECIL BERBASIS POTENSI LOKAL (APLIKASI MODEL PADA KEPULAUAN RAAS, GAYAM, DAN NONGGUNONG DI KABUPATEN SUMENEP) - Sutikno, . (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2013)
To the effect that wants to be reached deep observational it is: (a ) Identify isle economy potencies (b ) Determine superior commodity that can be made as individuality on isles (c ) Determines tipologi potencies based isles economic and utility farms (zonasi is farm); (d. ) Determines satuan isle development regions bases economic potency equalities and geographical positions. Base identification and analisis is region 3 isles, therefore developmental model design isle are as follows: Isle development that is at Sumenep's Regency is directed to formation five strategic regions, which is; (1 ) perikana's Areas conducting goes out to sea; (2 ) conducting developmental Areas brackish; 3 ) crossing port Areas and fishery; (4 ) tourism developmental Areas; and (5 ) conducting Area and lindung (Conservation) at coast and salt water.